Guidance regarding COVID‐19 for survivors of childhood, adolescent, and young adult cancer: A statement from the International Late Effects of Childhood Cancer Guideline Harmonization Group. Issue 12 (23rd September 2020) - Verbruggen, Lisanne C.; Wang, Yuehan; Armenian, Saro H.; Ehrhardt, Matthew J.; van der Pal, Helena J.H.; van Dalen, Elvira C.; van As, Jorrit W.; Bardi, Edit; Baust, Katja; Berger, Claire; Castagnola, Elio; Devine, Katie A.; et al.
Abstract: Childhood, adolescent, and young adult (CAYA) cancer survivors may be at risk for a severe course of COVID‐19. Little is known about the clinical course of COVID‐19 in CAYA cancer survivors, or if additional preventive measures are warranted. We established a working group within the International Late Effects of Childhood Cancer Guideline Harmonization Group (IGHG) to summarize existing evidence and worldwide recommendations regarding evidence about factors/conditions associated with risk for a severe course of COVID‐19 in CAYA cancer survivors, and to develop a consensus statement to provide guidance for healthcare practitioners and CAYA cancer survivors regarding COVID‐19.